2015
DOI: 10.1007/s00393-015-1641-y
|View full text |Cite
|
Sign up to set email alerts
|

Iguratimod in combination with methotrexate in active rheumatoid arthritis

Abstract: The data imply that iguratimod is a welcome addition to the small-molecule drug therapy for DMARD-experienced patients with active RA. Iguratimod (alone or in combination with MTX) is an emerging option for the treatment of DMARD-experienced adult patients with active RA who have had an inadequate response to or are intolerant of other DMARDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 17 publications
1
44
0
Order By: Relevance
“…Two 24-week clinical studies both showed similar results. The group of IGU combined with MTX had better outcomes than that of MTX alone, such as Patient's clinical manifestations including joint tenderness and swollen joint count, pain visual analogue scale overall assessment of patients and physicians, ESR, CRP, health assessment questionnaire, DAS28, simplified disease activity index, and ACR 50 (P < 0.05) ( Table 2) (Duan et al, 2015;Xia et al, 2016). Interestingly, there was no significant difference in the incidence of adverse events between the IGU+MTX group and the MTX group (P > 0.05).…”
Section: Igu Combined With Other Drugs Igu Combined With Mtxmentioning
confidence: 99%
“…Two 24-week clinical studies both showed similar results. The group of IGU combined with MTX had better outcomes than that of MTX alone, such as Patient's clinical manifestations including joint tenderness and swollen joint count, pain visual analogue scale overall assessment of patients and physicians, ESR, CRP, health assessment questionnaire, DAS28, simplified disease activity index, and ACR 50 (P < 0.05) ( Table 2) (Duan et al, 2015;Xia et al, 2016). Interestingly, there was no significant difference in the incidence of adverse events between the IGU+MTX group and the MTX group (P > 0.05).…”
Section: Igu Combined With Other Drugs Igu Combined With Mtxmentioning
confidence: 99%
“…After subsequent screening, an additional 33 were excluded: 30 randomized controlled trials (RCTs) did not include the ACR20/50/70, 2 RCTs did not report adverse events, and 1 RCT was repeated in more than one bibliographic source. After the selection process, a total of 7 RCTs consisting of 665 participants with 368 participants in the active arm and 297 in the placebo arm were included in the meta-analysis [1,[16][17][18][19][20][21]. A Preferred Reporting Items for Systematic Reviews and Meta-Analyses flow diagram is included in .…”
Section: Search Resultsmentioning
confidence: 99%
“…Two studies [1,20] allowed the use of one NSAID (0.2 g celecoxib capsule, two times a day, oral) and (or) a small dose of a glucocorticoid (prednisone 7.5 mg/d or 10 mg/d), and two studies allowed the ), respectively (. Fig.…”
Section: Characteristics Of Participants Interventions and Comparator Details In The Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Xia et al studied 131 Chinese patients with active RA who had previous exposure to other DMARDs. 75 The authors found that iguratimod combined with MTX had a significant synergistic effect on RA amelioration compared with MTX alone, whereas iguratimod alone was also efficient. The dose used was 25 mg twice a day orally for iguratimod and 10 mg weekly for MTX.…”
Section: Introductionmentioning
confidence: 99%